Evaluation of the Implementation of Inclusive Education at Piloting Elementary School, Bontang City - Darwis, Anissaa Alhaqqoh; Mulawarman, Widyatmike Gede; Haryaka, Usfandi (Lembaga Yasin AlSys, 2025)
The implementation of inclusive education is a priority in Indonesia to provide equitable and quality education for all citizens without discrimination. In Bontang City, this is regulated in Mayor Regulation Number 1 of 2013 which aims to fulfill the right to education for all children. In 2013, SDN 003 Bontang Utara and SDN 010 Bontang Selatan were designated as pilot schools for inclusive education. Over time, the number of Special Schools (SLB) increased from 3 to 6, with Students with Special Needs (PDBK) at SLB Negeri Bontang reaching almost 200 students. Evaluative research on the implementation of inclusive education in Bontang City used a qualitative approach with the CIPP (Context, Input, Process, Product) Stufflebeam evaluation model. Data were collected through interviews, observations, and documents, and tested through triangulation and audits by supervisors. The results showed that SDN 003 Bontang Utara was in Quadrant II (Unfocused Implementation) with input and products not yet meeting standards. SDN 010 Bontang Selatan is in Quadrant I (Dropout Implementation) with all aspects rated negative. Recommendations include strengthening the implementation of inclusive programs in SDN 003 and comprehensive improvements in SDN 010, including teacher training, provision of facilities, and intensive assistance from the government to build better inclusive education.